PETROLOGIC DISTRIBUTIONS ON THE MOON: BASED ON THE LUNAR PROSPECTOR (LP) GAMMA-RAY SPECTROMETER DATA TRANSFORMATION - Li Y.Q.; Ouyang Z.Y.; Liu J.Z.; Li C.L.; Zou Y.L. (My University, 2007)
The Apollo and LP gamma-ray Spectrometers have gained 10 types of element distributions on lunar surface, through syncretize gamma-ray Spectrometer data to lunar rocks and meteorolites chemical compostion data. We obtain ternary-diagram approach to build relationships between elements and petrologic types. At the same time, use the syncretized data to plot global petrologic distributions of mare basalt, plagioclase, KREEP rock and Mg-rich rock on the moon.
Keywords: DATA TRANSFORMATION; DISTRIBUTIONS; GAMMA-RAY SPECTROMETER; LUNAR ROCKS